Adolescent autoimmune encephalitis with dual positive anti-Drebrin and anti-mGluR2 antibodies: a case report - Liu, Anran; Huang, Jiarui; Zhang, Jianqiang; Yan, Junqiang (Frontiers in Immunology, 2026)
To date, no research has reported the coexistence of anti-Drebrin antibody and anti-mGluR2 antibody in patients with autoimmune encephalitis (AE). This study presents the first detailed case of AE with dual positivity for these antibodies, aiming to enrich the database of double antibody-positive AE and provide clinical insights for diagnosis and treatment. We report a 15-year-old male patient whose main clinical manifestations were mental abnormalities and epileptic seizures, accompanied by frequent irritability and rambling speech. Serological and cerebrospinal fluid (CSF) analyses showed positive results for Drebrin and mGluR2 antibodies. The titer of anti-Drebrin antibody was 1:1000 (serum) and 1:1 (CSF), while the titer of anti-mGluR2 antibody was 1:32+ (serum) and 1:1+ (CSF). Based on the clinical manifestations and diagnostic results, the patient was diagnosed with AE, with concurrent positive anti-Drebrin and anti-mGluR2 antibodies in both serum and CSF. Significant improvement was achieved following immunotherapies, including steroid pulse therapy and intravenous immunoglobulin infusion. Readmission one month later for relapse responded well to renewed immunotherapy, and the patient was discharged with marked improvement. No recurrence was observed during follow-up.